Land Use Systems and Soil Properties in Mokokchung District of Nagaland, India - Y.K. Sharma (Journal of the Indian Society of Soil Science, 2022)
Present investigation was conducted during 2017-18 to study the impact of different land use systems on soil properties. A total of seventy two surface soil samples were collected from twelve villages of six hill ranges of Mokokchung district of Nagaland, India. The soil samples were collected from the fields of jhum, settled and forest land use systems and were analyzed for different properties. Results revealed that the soils were strongly to moderately acidic in reaction and low in cation exchange capacity (CEC) and forest soils showed higher CEC than that of soils of jhum and settled land uses. Almost similar values of bulk density and porosity were reported in the soils of all land uses. On the basis of nutrient index, soils of all three land uses were high in organic carbon (OC), medium in available nitrogen (N), potassium (K) and sulphur (S), except jhum soils for phosphorus (P) and settled soils for sulphur (S), which were high and low in P and S status, respectively. Forest soils contained high amount of OC, available N, P, K, S and exchangeable calcium (Ca) and magnesium (Mg) than other soils. Available N, P, K, S, Ca and Mg were significantly and positively correlated with OC. Available P, Ca and Mg of the soils of all three land uses and N and S of settled soils had significant and positive correlations with soil pH. Total potential acidity of the soils was quite high and accounted for severe acidity problem in these soils. Reasonable quantity of various forms of acidity was reported in the soils. Quantum of various forms of acidities was high in forest soils except extract acidity, which was recorded high in jhum soils. Significant and negative correlation was observed among acidity components and soil pH. Extractable acidity in settled soils and exchangeable aluminium (Al3+) in settled and forest soils showed significant negative correlation with OC.